Показники спермопродуктивності та морфо-фізіологічні параметри сперми бугаїв голштинської породи - Сірацький, Й.З.; Бойко, О.В.; Кузебний, С.В.; Федорович, В.В. (Фактори експериментальної еволюції організмів, 2013)
Aims. The purpose of research – set features production of sperm bulls high producing dairy breeds and assess reproductive ability on physiological parameters of semen bull-sires. Methods. The intensity of respiration was determined polarographic, resistance spermatozoa – by adding 1 % sodium-term chloride, the number of live and dead spermatozoa – by counting under the microscope differentially dyed 5 % solution of eosin sex cells, sperm survival in hours – at t = 38 °C after thawing. Results. Differences production of sperm and physiological indicators of bull-sires semen related to their age and suit, and conducted correlation and regression analysis between the major quantitative and qualitative indicators production of sperm bulls high producing dairy breeds and physiological parameters of semen. Conclusions. These results suggest that the physiological parameters of bull sperm increased with age and were associated with indicators production of sperm bull-sires of Holstein breed.